Ionic Liquid Activation of Amorphous Metal‐Oxide Semiconductors for Flexible Transparent Electronic Devices. (9th February 2016) - Pudasaini, Pushpa Raj; Noh, Joo Hyon; Wong, Anthony T.; Ovchinnikova, Olga S.; Haglund, Amanda V.; Dai, Sheng; Ward, Thomas Zac; Mandrus, David; Rack, Philip D.
Abstract : Amorphous metal‐oxide semiconductors offer the high carrier mobilities and excellent large‐area uniformity required for high performance, transparent, flexible electronic devices; however, a critical bottleneck to their widespread implementation is the need to activate these materials at high temperatures which are not compatible with flexible polymer substrates. The highly controllable activation of amorphous indium gallium zinc oxide semiconductor channels using ionic liquid gating at room temperature is reported. Activation is controlled by electric field‐induced oxygen migration across the ionic liquid‐semiconductor interface. In addition to activation of unannealed devices, it is shown that threshold voltages of a transistor can be linearly tuned between the enhancement and depletion modes. Finally, the first ever example of transparent flexible thin film metal oxide transistor on a polyamide substrate created using this simple technique is demonstrated. This study demonstrates the potential of field‐induced activation as a promising alternative to traditional postdeposition thermal annealing which opens the door to wide scale implementation into flexible electronic applications. Abstract : Field induced activation of amorphous indium gallium zinc oxide is demonstrated for flexible transparent thin film transistor applications. The activation process is controlled by field induced oxygen migration across the ionic liquid‐semiconductor interface. Field‐induced activation shows potential as a promising alternative to traditional postdeposition thermal annealing which opens the door to wide scale implementation into flexible electronic applications.